The place of constitutionalism in the education of public administrators - Maletz, Donald J
The American Society for Public Administration's code of professional ethics culminates in an admonition to respect, support, and even study constitutions, both state and federal. However, an understanding of constitutionalism is an often neglected or perfunctory element in the educational programme for public administrators. In his influential 1887 essay on public administration, Woodrow Wilson reasoned that because there is near universal agreement about constitutional principles in modern society, concentration should be chiefly on problems of effective management. The recent rebirth of concern for education in professional ethics generally and ethics in public administration in particular also reveals a
Keywords: Ethics; Bureaucracy; Education; Civil Service - Training - USA